Dr. Peter Lennox — Deep Plane Facelift — Vancouver - Lennox, Peter (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Peter Lennox, practicing in Vancouver, Canada. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003428; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; canada; vancouver